2006
DOI: 10.1007/s10526-006-9026-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of two endoparasitic wasps, Hyposoter didymator and Chelonus inanitus, on the growth and food consumption of their host larva Spodoptera littoralis

Abstract: The influence of parasitism by Hyposoter didymator (Thunberg; Hymenoptera: Ichneumonidae) and Chelonus inanitus (Linnaeus) (Hymenoptera: Braconidae) on the growth and food consumption of their host Spodoptera littoralis (Boisduval) (Lepidoptera: Noctuidae) was studied in the laboratory. Parasitised larvae consumed significantly less artificial diet than unparasitised ones. Egg parasitisation by C. inanitus affected host larval consumption from the second day after emergence and it was significantly different f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…For example, five parasitoids of S. frugiperda , namely Aleiodes laphygmae (Viereck) , Campoletis sonorensis (Cameron), Chelonus insularis (Cresson) , Cotesia marginiventris (Cresson) and Meteorus laphygmae (Viereck), decreased larval feeding by at least 80% [30]. This was also reported for the congeneric species Spodoptera littoralis (Boisduval), where food consumption and growth were significantly reduced by the endoparasitoids Hyposoter didymator (Thunberg) and Chelonus inanitus (Linnaeus) [31]. The effect of parasitism by C. luteum on S. frugiperda larvae could result from the different mechanisms associated with the parasitism process.…”
Section: Discussionmentioning
confidence: 71%
“…For example, five parasitoids of S. frugiperda , namely Aleiodes laphygmae (Viereck) , Campoletis sonorensis (Cameron), Chelonus insularis (Cresson) , Cotesia marginiventris (Cresson) and Meteorus laphygmae (Viereck), decreased larval feeding by at least 80% [30]. This was also reported for the congeneric species Spodoptera littoralis (Boisduval), where food consumption and growth were significantly reduced by the endoparasitoids Hyposoter didymator (Thunberg) and Chelonus inanitus (Linnaeus) [31]. The effect of parasitism by C. luteum on S. frugiperda larvae could result from the different mechanisms associated with the parasitism process.…”
Section: Discussionmentioning
confidence: 71%
“…Insects express robust immune reactions to parasitoid eggs and research has focused on the actions of maternal factors that mediate host immunosuppression following deposition of parasitoid eggs 3 . Reports on endocrine mechanisms responsible for changing feeding behaviors and development are relatively scant 4 5 6 7 8 .…”
mentioning
confidence: 99%
“…Moreover, C. inanitus manipulates the host development because parasitized larvae grow less than non-parasitized ones, due to the drastic reduction in food consumption since the early stages [21,30]. It has been reported that the final body weight of parasitized S. littoralis larvae only reaches 13% of the maximum weight of non-parasitized sixth-instar larvae [54]. Therefore, even though C. inanitus is an extreme koinobiont that kills the host in an advanced developmental stage, parasitized larvae cause less damage to plants.…”
Section: Discussionmentioning
confidence: 99%